The fast track land reform programme: Reflecting on the challenges and opportunities for resettled former farm workers at Fairfield farm in Gweru district, Zimbabwe - Mutema, Edson Paul (Clarion University of Pennsylvania, 2021)
This paper uses a purposively sampled case study of Fairfield farm in Gweru district, Zimbabwe to explore the challenges and opportunities of Resettled Former Farm Workers (RFFW).Resettlement of former farm workers was done by the Government of Zimbabwe in order to promote sustainable local economic development and livelihoods. Prior to resettlement these former farm workers were living in poverty characterised by poor wages paid by white farmers. To obtain primary data the study utilised in – depth interviews on a convenient sample of 20 Resettled Former Farm Workers and participant observation. This was further complimented by secondary data from an extensive relevant literature study. The study reveals that despite the government’s noble idea of giving Former Farm Workers land so that they can pursue sustainable livelihood, the RFFW are experiencing a number of challenge that impede sustainable farm production. These include, inaccessible roads, poor water and sanitation facilities, poor harvests due to lack of capital to buy inputs and farming equipment, vulnerability to periodic droughts and floods, an insecure land tenure system and clinics and schools which are distanced and poorly resourced. Apart from the fore mentioned challenges this paper further reveals the following opportunities on the livelihood improvement for the RFFW, access to land, basic education for their kids, permanent homes, and improved lifestyles. The paper concludes by recommending that the Government of Zimbabwe should prioritise infrastructure development in newly resettled areas. Donors should be invited to build schools, clinics, roads, and bridges in newly resettled areas. Given their vulnerable and disadvantaged background RFFW need capital interventions and commercial agriculture training from the government and donors to profitably and sustainably execute their farming operations. Finally the Government of Zimbabwe should resolve the issue of insecurity of tenure in its newly resettled areas.